ANASTROZOL EFFECTS ON THE HISTOMORPHOLOGY OF RABBIT LENS: Anastrozol Effects - Qamar, Dr Khadija; Khalil, Aamna; Umbreen, Faiza; Zia, Muhammad Sarwar (Pakistan Armed Forces Medical Journal, 2018)
Objective: To evaluate the effects of prolonged use of anastrozole as an endocrine treatment of breast cancer on the lens in an animal model. Study Design: Randomized control trial. Place and Duration of Study: Department of Anatomy Army Medical College, Rawalpindi in collaboration with National Institute of Health Islamabad, 6 months from Jun 2012 to Nov 2012. Material and Methods: Twenty adult female NewZealand white rabbits were taken. Ten rabbits were placed in control group A and 10 placed in group B and were given anastrozole orally in the normal dose. After the completion of the study, both eyes of each animal were enucleated and lenses removed and grossly examined. The specimens were fixed and processed and slides prepared for histological examination. The lenses were carefully examined for any opacities. Thickness and diameter of the lenses were measured for each eye. The results were compared between the groups for statistical significance by using SPSS version 21. Results: The lenses in the experimental group were found to be transparent with no opacities. In the experimental group B, the mean diameter of lenses was 10.42 ± 0.51 μm for the right eye and 10.43 ± 0.49 μm in the left eye. Mean thickness of the lenses in group B was 6.48 ± 0.43 μm and 6.46 ± 0.44 μm for the right and left eye, respectively. The p-values in the comparison between the control and the experimental group was statistically insignificant. Conclusion: Ocular side effects are quite common even in systemically administered cancer medication. Long term administration of Anastrozole has no effect on the histomorphology of the lenses of the eye.